2019
DOI: 10.3390/beverages5040069
|View full text |Cite
|
Sign up to set email alerts
|

Red Rooibos Tea Stimulates Osteoblast Mineralization in a Dose-Dependent Manner

Abstract: Most studies show a positive association between higher tea intake and bone mineral density (BMD), while associations with fracture are inconclusive. Although a few studies have investigated the potential effects of rooibos tea on the bone cell metabolism, only 1 or 2 doses were tested or specific flavonoids were evaluated in isolation. A dose-response study is needed to comprehensively identify whether a level that modulates bone cell activity is associated with dietary or supplemental levels of red rooibos (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Cellular viability was measured through cellular activity using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay after 24 and 48 h of cell exposure to BT (0.1, 0.5, 0.75, 1, 2, 5, or 10 μ g GAE/mL) or control vehicle. 17 , 18 After 24 h, Saos-2 cells displayed a significantly higher cellular activity ( P < .05) at concentrations 2–10 μ g GAE/mL. There was a dose-dependent response of BT doses at 24 h (CON, 0.1, 0.5, 0.75, 1, 2, 5, 10 μ g GAE/mL).…”
Section: Methods Results and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Cellular viability was measured through cellular activity using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay after 24 and 48 h of cell exposure to BT (0.1, 0.5, 0.75, 1, 2, 5, or 10 μ g GAE/mL) or control vehicle. 17 , 18 After 24 h, Saos-2 cells displayed a significantly higher cellular activity ( P < .05) at concentrations 2–10 μ g GAE/mL. There was a dose-dependent response of BT doses at 24 h (CON, 0.1, 0.5, 0.75, 1, 2, 5, 10 μ g GAE/mL).…”
Section: Methods Results and Discussionmentioning
confidence: 93%
“…Expression of proteins of interest (alkaline phosphatase [ALP], osteopontin [OPN], ectonucleotide pyrophosphatase/ phosphodiesterase-1 [NPP1]) was determined at day 3 of mineralization through immunoblotting using a previously established protocol. 17 was 1:10000 (ab205718) in 5% BSA/TBST (ALP and NPP1) or 5% milk/TBST (OPN) (Abcam, Cambridge, UK). Protein signals were detected with the ChemiDoc Imaging System (Bio-Rad, Mississauga, ON, Canada) and densitometry analysis was performed using Image Studio Lite software (LICOR Biosciences, Lincoln, NE, USA).…”
Section: Methods Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of tea and its specific polyphenols on both osteoblasts and osteoclasts have been studied using cell models. [11][12][13][14][15][16][17][18][19] The majority of studies using osteoblasts have studied the effects of green or black teas and have consistently shown increases in mineralization in response to tea. More specifically black, green, and rooibos (red and green) teas have been shown to increase mineralization at concentrations likely attainable through diet.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically black, green, and rooibos (red and green) teas have been shown to increase mineralization at concentrations likely attainable through diet. [11][12][13] As well, individual polyphenols and extracts derived from black, green, and rooibos teas have been studied and demonstrate a capacity to increase mineralization; however, the concentrations required to demonstrate these effects are usually at a level that would require supplementation. [14][15][16] While studies in osteoclasts are limited, previously published studies have shown that black, green, or green rooibos teas elicit a decrease in activity.…”
Section: Introductionmentioning
confidence: 99%